Reflective Journal to Explore Instructional Practices in an Online Writing Class: Students’ Perspective - Yuniatri Intan Kusuma Ningrum; Niamika El Khoiri; Nova Ariyani; Nur Mukminatien (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2022)
Abstract: This study explored reflective journals of Indonesian EFL undergraduate students aiming to investigate a teacher’s instructional practices in online writing classes. Using the narrative methodology, the data were collected from students’ reflective journals, recorded interviews, and a questionnaire. This study found that teachers’ instructional practices have assisted students during the learning process, for instance, the integration of technology makes students more engaged. This study also observed students’ challenges during online classes, such as the unsupportive learning environment which covers studying alone and household chores distraction. This study offers insight for teachers that students’ reflective journal helps evaluate the instructional practice and improve teaching quality.